2015
DOI: 10.1016/j.jsat.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Homeless and Non-Homeless Problem Drug Users Recruited from Primary Care Safety-Net Clinics

Abstract: Introduction The present study of homeless non-treatment-seeking problem drug users was designed to complement and extend previous studies which focused exclusively on treatment-seeking homeless problem drug users. Method Data were available for 866 primary care patients with drug problems, 30% homeless and 70% housed. Results In the 2 years prior to baseline, homeless participants had less chronic medical co-morbidity than problem drug users who were housed yet were significantly more likely to have used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…One study found that 22.8% of ED patients with high-risk substance use were homeless, but no comparison was given for patients without high-risk use (Hankin et al, 2013). Our findings are consistent with research conducted in other groups including primary care patients, and Veterans and others entering substance use treatment (Buchholz et al, 2010; Eyrich-Garg et al, 2008; Krupski et al, 2015; Welte and Barnes, 1992). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One study found that 22.8% of ED patients with high-risk substance use were homeless, but no comparison was given for patients without high-risk use (Hankin et al, 2013). Our findings are consistent with research conducted in other groups including primary care patients, and Veterans and others entering substance use treatment (Buchholz et al, 2010; Eyrich-Garg et al, 2008; Krupski et al, 2015; Welte and Barnes, 1992). …”
Section: Discussionsupporting
confidence: 90%
“…Prior studies have been limited to including only participants who have experienced homelessness or those seeking substance use treatment. One exception, a study of primary care patients with drug problems, found that patients experiencing homelessness had higher DAST-10 and ASI scores, and used the emergency department (ED) more frequently than other patients (Krupski et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous violence victimization might trigger development of drug use disorders, which might in turn lead to later perpetration of violence ( 35–39 ). Moreover, structural causes of drug use problems are relevant, given that they have been linked to criminalization ( 23 ), as well as factors such as poverty ( 40 ), poor mental health ( 4 , 41 ), treatment availability ( 42 ), and homelessness ( 43 ). In addition, physical and psychological effects of drugs can lead to agitation, aggression, and cognitive impairment that might in turn heighten risk of violence.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of reasons for these outcomes. In comparison to the general population, people who are homeless are more likely to have multiple chronic comorbidities (Lebrun-Harris et al, 2013), high rates of problematic substance use (Krupski et al, 2015;Lebrun-Harris et al, 2013), and poor nutrition (Fallaize et al, 2017). People who are homeless often live in outdoor, informal and highly-congregate settings, among transient populations, and without access to adequate hygiene facilities (Tsai & Wilson, 2020).…”
Section: Health Disparities and Vaccine-preventable Diseases In Peoplmentioning
confidence: 99%